Nuclear medicine in Malaysia – strengths and challenges for physicians after more than half a century of experience - Suppiah, Subapriya (Malaysian Medical Association, 2021)
Nuclear medicine (NM) has been established in Malaysia for almost 60 years. It is a specialty that utilizes radiopharmaceuticals for theranostics, by the assessment of bodily functions to diagnose certain diseases and conditions particularly in oncology, cardiology, and neurology as well as to provide therapeutic solutions in certain instances. The strengths of NM include the establishment of various nuclear medicine centres throughout the country, including in Sabah and Sarawak, particularly for general nuclear medicine, and the mushrooming of positron emission tomography computed tomography (PET/CT) centres along the states in the west coast of Malaysia, the institution of a formal national nuclear medicine physician training programme, and collaboration with international bodies to develop theranostic services. The challenges for NM ahead are namely regulatory and financial constraints for utilizing newer radiopharmaceuticals available in the international market, expansion of accredited training programmes to produce skilled healthcare workforce, optimization of resources at hand and multidisciplinary collaborations to reduce premature mortality of patients caused by noncommunicable diseases, particularly cancer.